CONVERSION INTENTION KONSUMEN PADA META ADS : PERAN PERSONALIZED ADVERTISING, PERCEIVED RELEVANCE DAN E-WOM - Muzakkir Akbar; Muhammad Rasyid Ridho; Nadia Ulfa; Rohmadi Rohmadi (ISTISMAR, 2026)
This study aims to analyze consumer conversion intention on Meta Ads in Indonesia. The study employed a quantitative approach using primary data collected through questionnaires distributed to Facebook and Instagram users who had previously viewed or interacted with Meta Ads. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The findings reveal that Personalized Advertising and Perceived Relevance have a positive and significant effect on consumers’ Conversion Intention on Meta Ads. Meanwhile, Electronic Word of Mouth (e-WOM) has no significant effect on Conversion Intention. Furthermore, e-WOM is unable to moderate the relationship between Personalized Advertising and Conversion Intention, as well as the relationship between Perceived Relevance and Conversion Intention. The findings provide a deeper understanding of the factors influencing consumer Conversion Intention within the Meta Ads ecosystem. This study contributes to the digital marketing literature by highlighting the importance of personalized and relevant advertising in enhancing consumer conversion. The results are expected to serve as a reference for business practitioners and digital marketers in designing more effective advertising strategies through the optimization of advertisement personalization and relevance to encourage consumer conversion. Keywords: Personalized Advertising, Perceived Relevance, Electronic Word of Mouth, Conversion Intention, Meta Ads